Patent-backed debt finance: should company law take the lead to provide a "true and fair" view of SME patent assets? - Denoncourt, Janice A. (2015)
The most important high technology intellectual property (IP) rights in terms of innovation are patents,a form of intangible property right. Even though these corporate assets drive 21st century technological innovation, patent-backed lending to UK SMEs remains underdeveloped. One reason is that the value of their internally generated patents is under-reported in traditional financial statements due to the application of International Accounting Standard 38 Intangibles. The accounting problem is exacerbated by the fact that SMEs are exempt from company law requirements to present a directors’ Strategic Report in their annual return to Companies House. The astonishing lack of quantitative and qualitative public information about corporate IP assets makes it difficult to assess their strategic value (“the patent value story”) and directors’ stewardship of those assets. While this may restrict access to debt finance, this thesis argues there is a wider corporate governance issue. More relevant, accurate and timely corporate IP information (mostly known to internal management) is needed to triangulate intangibles financial data through cross verification with corporate narrative disclosure. The multidisciplinary insights into the transparency corporate problem and how directors fulfil existing obligations to provide “true and fair” IP information under UK law provide an academic audience with a deeper level of legal analysis concerning the intersection between: (1) the patent ecosystem; (2) accounting for intangibles; (3) patent-backed debt finance; and (3) corporate disclosure. Knowledge is advanced with an original business triage style Essential, Desirable & Optional narrative corporate disclosure model.